Show that sec'x = d/dx (sec x) = sec x tan x.
First, take note that
sec x = 1/cos x;
d sin x = cos x dx;
d cos x = -sin x dx; and
d log u = du/u.
From the last, we have du = u d log u.
Then, letting u = sec x, we have,
d sec x = sec x d log sec x; and
d log sec x = d log ( 1 / cos x )
= -d log cos x
= d ( -cos x ) / cos x
= sin x dx / cos x
= tan x dx.
Thence, d sec x = sec x tan x dx, and
sec' x = sec x tan x,
which is what we set out to show.
d/dx sec(2x) = 2sec(2x)tan(2x)
Given y = tan x: dy/dx = sec^2 x(secant of x squared)
Rewrite sec x as 1/cos x. Then, sec x sin x = (1/cos x)(sin x) = sin x/cos x. By definition, this is equal to tan x.
f'(x) = 1/tan(x) * sec^2(x) where * means multiply and ^ means to the power of. = cot(x) * sec^2(x) f''(x) = f'(cot(x)*sec^2(x) + cot(x)*f'[sec^2(x)] = -csc^2(x)*sec^2(x) + cot(x)*2tan(x)sec^2(x) = sec^2(x) [cot(x)-csc^2(x)] +2tan(x)cot(x) = sec^2(x) [cot(x)-csc^2(x)] +2
f(x)= tan2(x) f'(x)= 2tan(x)*sec2(x)
The derivative of sec(x) is sec(x) tan(x).
sec(x)tan(x)
d/dx sec(2x) = 2sec(2x)tan(2x)
the derivative of tangent dy/dx [ tan(u) ]= [sec^(2)u]u' this means that the derivative of tangent of u is secant squared u times the derivative of u.
d/dx(uv)=u*dv/dx+v*du/dxd/dx(secxtanx)=secx*[d/dx(tanx)]+tanx*[d/dx(secx)]-The derivative of tanx is:d/dx(tan u)=[sec(u)]2*d/dx(u)d/dx(tan x)=[sec(x)]2*d/dx(x)d/dx(tan x)=[sec(x)]2*(1)d/dx(tan x)=(sec(x))2=sec2(x)-The derivative of secx is:d/dx(sec u)=[sec(u)tan(u)]*d/dx(u)d/dx(sec x)=[sec(x)tan(x)]*d/dx(x)d/dx(sec x)=[sec(x)tan(x)]*(1)d/dx(sec x)=sec(x)tan(x)d/dx(secxtanx)=secx*[sec2(x)]+tanx*[sec(x)tan(x)]d/dx(secxtanx)=sec3(x)+sec(x)tan2(x)
It helps to convert everything to sines and cosines. Then you can often do lots of simplifications.Reminder: sec A = 1 / cos A tan A = sin A / cos A cosec A = 1 / sin A If you are unsure whether the two actually ARE equal, try evaluating both expressions (left and right) for some arbitrary value (for example, 10 degrees). If the two are NOT equal, then the expression are of course NOT equal. But if they ARE equal, you still need to prove that - since the claim is basically that the expressions are equal for ALL values of the variable.
Given y = tan x: dy/dx = sec^2 x(secant of x squared)
these are the identities i need sinΘcosΘ=cosΘ sec^4Θ-tan^4Θ=sec²Θcsc²Θ (1+sec²Θ)/(1-secΘ)=(cosΘ-1)/(cosΘ)
The derivative of tan(x) is sec2(x).(Which is the same as 1/cos2(x).
It is NOT equal. Try calculating tan x, and tan 6x, for a few values of "x", on your scientific calculator. Perhaps you are supposed to solve an equation, and see FOR WHAT values of "x" the two are equal?
Rewrite sec x as 1/cos x. Then, sec x sin x = (1/cos x)(sin x) = sin x/cos x. By definition, this is equal to tan x.
Note that for sec²(x) - tan²(x) = 1, we have: -tan²(x) = 1 - sec²(x) tan²(x) = sec²(x) - 1 Rewrite the expression as: ∫ (sec²(x) - 1) dx = ∫ sec²(x) dx - ∫ 1 dx Finally, integrate each expression to get: tan(x) - x + K where K is the arbitrary constant